If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (11m + -4n)(4m + 8n) = 0 Multiply (11m + -4n) * (4m + 8n) (11m * (4m + 8n) + -4n * (4m + 8n)) = 0 ((4m * 11m + 8n * 11m) + -4n * (4m + 8n)) = 0 Reorder the terms: ((88mn + 44m2) + -4n * (4m + 8n)) = 0 ((88mn + 44m2) + -4n * (4m + 8n)) = 0 (88mn + 44m2 + (4m * -4n + 8n * -4n)) = 0 (88mn + 44m2 + (-16mn + -32n2)) = 0 Reorder the terms: (88mn + -16mn + 44m2 + -32n2) = 0 Combine like terms: 88mn + -16mn = 72mn (72mn + 44m2 + -32n2) = 0 Solving 72mn + 44m2 + -32n2 = 0 Solving for variable 'm'. Factor out the Greatest Common Factor (GCF), '4'. 4(18mn + 11m2 + -8n2) = 0 Factor a trinomial. 4((11m + -4n)(m + 2n)) = 0 Ignore the factor 4.Subproblem 1
Set the factor '(11m + -4n)' equal to zero and attempt to solve: Simplifying 11m + -4n = 0 Solving 11m + -4n = 0 Move all terms containing m to the left, all other terms to the right. Add '4n' to each side of the equation. 11m + -4n + 4n = 0 + 4n Combine like terms: -4n + 4n = 0 11m + 0 = 0 + 4n 11m = 0 + 4n Remove the zero: 11m = 4n Divide each side by '11'. m = 0.3636363636n Simplifying m = 0.3636363636nSubproblem 2
Set the factor '(m + 2n)' equal to zero and attempt to solve: Simplifying m + 2n = 0 Solving m + 2n = 0 Move all terms containing m to the left, all other terms to the right. Add '-2n' to each side of the equation. m + 2n + -2n = 0 + -2n Combine like terms: 2n + -2n = 0 m + 0 = 0 + -2n m = 0 + -2n Remove the zero: m = -2n Simplifying m = -2nSolution
m = {0.3636363636n, -2n}
| 3056890000.00-15000000.00x=3000000 | | z^2-4z+1=0 | | q^2+6q=7 | | m^2-14m+30=6 | | 4m^4+4=17m^2 | | -72-5x+8x^2 | | a^2-8a+16=12 | | 3056890000.00-15000000x=3000000000 | | 12x^2=11x-2 | | r^2+4r+4=7 | | b^2+16b+64=9 | | 8z-3=2z | | 1/2(-16-4) | | y^2+2y+1=3 | | 90=(2w+3)(w) | | 4a+4b+2c=-8 | | W^2-10W+25=16 | | 69*67=x | | 15a^2-27n-6=0 | | 69*67= | | 11z-5=8z+7 | | X~-4-1=7 | | 4x+5x=29 | | 5m^2=85m | | -57+9x=41+2x | | −11=4−2r−5 | | m-3/8 | | 3x^2-41x+60=0 | | 2x^2+3x-32=0 | | -13x-6=-97 | | (2v+9)(3+v)=0 | | 3a−1−3=5 |